Experience-Based Value Construction Learning Intervention in Enhancing Prosocial Character among Vocational Healthcare Candidates - Silmi Kapatan Inda Robby; Euis Reliyanti Arum; Siti Fauziah (Journal of Pedagogy and Education Science, 2026)
The modern healthcare sector demands both technical competence and strong moral integrity. Prosocial behavior—encompassing empathy, altruism, and responsibility—constitutes a fundamental pillar for healthcare personnel interacting directly with vulnerable patients. Empirical evidence indicates that 51% of vocational health students exhibit relatively low prosocial behavior, with no significant correlation to academic achievement, underscoring the need for evidence-based character interventions. This study applies a quasi-experimental pre-test and post-test control group design to causally evaluate the effectiveness of a structured, experience-based value construction intervention (10 sessions, 8–12 weeks) among vocational healthcare candidates at a single polytechnic institution in Bandung. The Prosocial Character Scale demonstrated excellent internal reliability (Cronbach’s α = 0.927). Descriptive statistics revealed meaningful between-group differences: the Experimental group (n = 52) achieved a post-test mean of 73.76 (SD = 5.20, Min = 62, Max = 85) compared to the Control group (n = 51) at 70.25 (SD = 4.90, Min = 61, Max = 82). Analysis of Covariance (ANCOVA), controlling for baseline scores, yielded a statistically significant intervention effect (F(1, 100) = 15.50, p < 0.001), with a large effect size (η² = 0.134). These findings provide strong causal evidence for a replicable, experience-based approach to prosocial character development in health vocational education.